Pengembangan Virtual Exhibition Sebagai Edukasi Kewirausahaan dan Technopreneurship - Rizka Dewi Auliya; Ika Zutiasari (Universitas Negeri Padang, 2023)
This research aims to produce a virtual exhibition media that is valid and feasible to use as entrepreneurship and technopreneurship education to students. The background of the research is the application of technopreneurship learning which is still not optimally implemented in universities. Based on observations, there is student interest in learning entrepreneurship and new innovations. This research includes development research with ADDIE stages. The test subjects of this research were 100 students of the Department of Management with snowball sampling technique. Data collection instruments include observation, questionnaire, documentation. The types of data used are qualitative and quantitative data with quantitative descriptive statistical data analysis techniques. The overall validation results from media experts and material experts obtained an average score of 95.5% with the criteria